Screening of antimicrobial activity of bacteria from natural habitats to control Xanthomonas campestris pv. campestris in cabbage - Liu, Jian (2017)
The black rot disease is a serious disease on Brassica oleracea caused by Xanthomonas campestris pv. campestris. The majority of cabbages were affected by black rot disease and caused economic losses in Malaysia. The problem I am trying to solve in this study is to use potential bacteria culture to inhibit the Xanthomonas campestris pv. campestris growth. The approach which I adopted is antimicrobial susceptibility test (AST). A total of 106 bacteria samples were used for AST. Each sample was repeated twice. Result showed that 32 bacteria have the potential to control Xanthomonas campestris pv. campestris in vitro. The data were analyzed with ANOVA and mean separations of LSD tests using SAS 9.4. Sample No.12, No.15, No. 24 and No.28 showed bigger size inhibition areas as compared to control. These four samples were also characterized for gram staining and identified using 16s rRNA molecular method. From identification result, No.12 was identified as Bacillus cereus; No.15 as Brevibacillus parabrevis. Bacteria No.24 and No.28 were identified as Bacillus subtilis.